Pharmaceutical Suspensions From Formulation Development to Manufacturing - Kulshreshtha, Alok K.; Singh, Onkar N.; Wall, G. Michael; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Suspension dosage form is a preferred and widely accepted dosage forms for insoluble or poorly soluble drugs for various therapeutic applications. The suspension dosage form has long been used for insoluble and poorly soluble drugs for making oral, topical and parenteral products. Pharmaceutical Suspensions, From Formulation Development to Manufacturing provides the reader with a broad overview of suspension drug product technology. Individual chapters in this book focus on suspension formulation principles, excipients, analysis, pharmaceutical development, preclinical, clinical and regulatory aspects, as well as the emerging technology of nanosuspensions as nanomedicine. Various chapters in the book are written by authors from academia, regulatory agencies and industries who are experts in their respective fields. The book includes over 600 bibliographic citations, numerous tables and illustrations. Pharmaceutical Suspensions is the only volume to date that systematically follows the suspension dosage development approach used widely in the pharmaceutical industries starting with pre-formulation/formulation development, pre-clinical evaluation and critical characterization method development, continuing to clinical trial essentials and ending with technology transfer essentials and regulatory filing guidance. Pharmaceutical Suspensions, From Formulation Development to Manufacturing provides a useful resource for pharmaceutical scientists, process scientists/engineers involved in the areas of research and development of pharmaceutical suspension dosage forms as well as for advanced pharmacy undergraduate and graduate students who want in-depth knowledge of suspension dosage form. "Solid useful text on suspension formulation development".
Various Pharmaceutical Disperse Systems -- General Principles of Suspensions -- Commonly Used Excipients in Pharmaceutical Suspensions -- Pharmaceutical Development of Suspension Dosage Form -- Preclinical Development for Suspensions -- Analytical Tools for Suspension Characterization -- Clinical Trials of Suspension Drug Products -- Scale Up and Technology Transfer of Pharmaceutical Suspensions -- The Science and Regulatory Perspectives of Pharmaceutical Suspensions -- Solid Nanosuspensions: The Emerging Technology and Pharmaceutical Applications as Nanomedicine.
Keywords: Pharmacology; Pharmacology/Toxicology.